Odpowiedzi

2009-12-08T16:38:47+01:00
A)
2x+y=13
x-1/2y=2×(-2)

2x+y=13
-2x+y=-4

2y=9
y=4,5
2x+4,5=13
x=4,25

b)
6x+9y=15
2x+3y=3/×(-3)

e)
1/3x+1/5y=2
x+0,6y=6

1/3x+15/10y=2
x+6/10y=6/×

c)
1/2x-y=1
x-2y=2

0=0
0=6brak rozwiązania

d)
1,5x+0,5y=2
0,3x+0,1y=2/3

15/10x+5/10y=2
3/10x+1/10y=2/3×(-5)

15/10x+5/10y=2
-15/10x-5/10y=-10/3
0=-4/3
e)
1/3x+1/5y=2
x+0,6y=6

1/3x+5/10y=2
x+6/10y=6/(-1/3)
1/3x+5/10y=2
-1/3x-6/10y=-2
9/30y=0
y=0
2009-12-08T16:42:13+01:00
A) 2x+y=13
x- 1/2 = 2 / *(-2)

2x+y=13
-2x+y=-4

2y=9
y=4,5
x=8,5

b)
6x+9y=15
2x+3y=3 /*(-3)

6x+9y=15
-6y-9y=-9
sprzeczne

c)
1/2x-y=1 /*(-2)
x-2y=2

x+2y=-2
x-2y=2
2x=0
sprzeczne

d)
1,5x+0,5y=2 /*10
0,3x+0,1=2/3 /*10

15x+5y=20
3x+y= 20/3 /*(-5)

15x+5y=20
-15x-5y= - 100/3
sprzeczne

e)
1/3x+1/5y=2 /*10
x+0,6y=6 /*10

10/3x +2y=20 /*(-3)
10x+6y=60

-10x-6y=60
10x+6y=60
sprzeczne
2009-12-08T18:38:57+01:00
A)
2x+y=13
x-1/2y=2 /'*2

2x+y=13
2x-y=4 dodajemy obustronnie
4x=17
x=4,25
y=13-2x
y=13-8,5=4,5

b)
6x+9y=15
2x+3y=3 /*3

6x+9y=15
6x+9y=9 równanie sprzeczne

c)
1/2x-y=1 => y=1/2x-1
x-2y=2

1/2x-y=1
x-x+2=2
0=0 równanie nieokreślone
d)
1,5x+0,5y=2 /*2
0,3x+0,1y=2/3 /*10

3x+y=4
3x+y=20/3 równanie sprzeczne

e)
1/3x+1/5y=2 /*3
x+0,6y=6

x+0,6y=6
x+0,6y=6 równanie nieokreślone